Influence of Organizational Commitment and Organizational Climate on Turnover Intenion of Employees at PT Nusatovel Semarang Head Office - Yusuf - Sutiyoso; Dody - Setyadi; Sugiyanta - Sugiyanta (Admisi dan Bisnis, 2023)
This study aimed to determine the influence of organizational commitment and organizational climate on turnover intention of employees at PT Nusatovel Semarang Head Office. The methods that used for data collection in this study were interviews and questionnaires. The scale that used in the questionnaires is agree disagree scale with 10 scale points. The sample that used in this study was 69 employees of PT Nusatovel Semarang Head Office. Used multiple linear regression techniques for analyzing the data, it indicated that organizational commitment and organizational climate had a negative and significant influence on turnover intention. organizational commitment and organizational climate had 42.4% contribution to turnover intention, that means every 42.4% of turnover intention was explained by organizational commitment and organizational climate, while 57.6% was explained by other factors which were not observed in this study